Association Between Measures Derived From Children's Primary Exfoliated Teeth and Psychopathology Symptoms: Results From a Community-Based Study - Dunn, Erin C.; Mountain, Rebecca V.; Davis, Kathryn A.; Shaffer, Ida; Smith, Andrew D. A. C.; Roubinov, Danielle S.; Den Besten, Pamela; Bidlack, Felicitas B.; Boyce, W. Thomas (Frontiers in Dental Medicine, 2022)
Mental disorders are among the most disabling health conditions globally. However, there remains a lack of valid, reliable, noninvasive, and inexpensive biomarkers to identify (at an early age) people who are at the greatest risk of experiencing a future mental health condition. Exfoliated primary teeth, when used in combination with established and emerging tools (e.g., family history, imaging, genetics, epigenetics), may provide important additional insights about vulnerability to mental illness. Teeth are especially promising because they develop in parallel with the brain and maintain a permanent record of environmental insults occurring during prenatal and perinatal development. Despite their potential, few empirical studies have investigated features of exfoliated teeth in relation to mental health. Here, we used micro-CT imaging to test the hypothesis that measures derived from exfoliated primary incisors associated with psychopathology symptoms in a community-based sample of children (N=37). We found that enamel volume (=-0.77, 95% CI, -1.35 to -0.18, P=.01) had large negative associations with internalizing symptoms and enamel mineral density (=0.77, 95% CI, 0.18 to 1.35, P=.01) had large positive associations with internalizing behavioral symptoms, even after stringent control for multiple testing. Pulp volume (=-0.50, 95% CI, -0.90 to -0.09, P=.02) had a moderately-large negative association with externalizing behavioral symptoms, though these associations did not survive multiple testing. These results support the ongoing investigation of teeth as potential novel biomarkers of mental health risk.